Generality of toxins in defensive symbiosis: Ribosome-inactivating proteins and defense against parasitic wasps in Drosophila - Ballinger, Matthew J.; Perlman, Steve J. (PLoS pathogens, 2017)
While it has become increasingly clear that multicellular organisms often harbor microbial symbionts that protect their hosts against natural enemies, the mechanistic underpinnings underlying most defensive symbioses are largely unknown. Spiroplasma bacteria are widespread associates of terrestrial arthropods, and include strains that protect diverse Drosophila flies against parasitic wasps and nematodes. Recent work implicated a ribosome-inactivating protein (RIP) encoded by Spiroplasma, and related to Shiga-like toxins in enterohemorrhagic Escherichia coli, in defense against a virulent parasitic nematode in the woodland fly, Drosophila neotestacea. Here we test the generality of RIP-mediated protection by examining whether Spiroplasma RIPs also play a role in wasp protection, in D. melanogaster and D. neotestacea. We find strong evidence for a major role of RIPs, with ribosomal RNA (rRNA) from the larval endoparasitic wasps, Leptopilina heterotoma and Leptopilina boulardi, exhibiting the hallmarks of RIP activity. In Spiroplasma-containing hosts, parasitic wasp ribosomes show abundant site-specific depurination in the α-sarcin/ricin loop of the 28S rRNA, with depurination occurring soon after wasp eggs hatch inside fly larvae. Interestingly, we found that the pupal ectoparasitic wasp, Pachycrepoideus vindemmiae, escapes protection by Spiroplasma, and its ribosomes do not show high levels of depurination. We also show that fly ribosomes show little evidence of targeting by RIPs. Finally, we find that the genome of D. neotestacea's defensive Spiroplasma encodes a diverse repertoire of RIP genes, which are differ in abundance. This work suggests that specificity of defensive symbionts against different natural enemies may be driven by the evolution of toxin repertoires, and that toxin diversity may play a role in shaping host-symbiont-enemy interactions.